Analysis and simulation of electrical and computer systems - Golebiowski, Leslaw; Mazur, Damian; SpringerLink (Online service).; Scientific Conference Selected Issues of Electrical Engineering and Electronics Rzeszów, Poland; Czarna, Poland) 2013 (Cham Springer International Publishing, 2015)
This book presents the selected results of the XI Scientific Conference Selected Issues of Electrical Engineering and Electronics (WZEE) which was held in Rzeszow and Czarna, Poland on September 27-30, 2013. The main aim of the Conference was to provide academia and industry to discuss and present the latest technological advantages and research results and to integrate the new interdisciplinary scientific circle in the field of electrical engineering, electronics and mechatronics. The Conference was organized by the Rzeszow Division of Polish Association of Theoretical and Applied Electrical Engineering (PTETiS) in cooperation with Rzeszow University of Technology, the Faculty of Electrical and Computer Engineering and Rzeszow University, the Faculty of Mathematics and Natural Sciences.
Electronic reproduction.
Keywords: System analysis -- Congresses; Computer simulation -- Congresses; Electronic books